Inpatient re-rupture of a middle meningeal arteriovenous fistula after traumatic brain injury - Piyush Goyal, BS; Amir Khan, MD (Radiology Case Reports, 2023)
We present a case of a spontaneous second intraparenchymal hemorrhage (IPH) following patient admission for a traumatic brain injury with an initial traumatic IPH. After a subsequent review of all imaging, it was concluded that the patient had a traumatic middle meningeal associated dural arterial venous fistula (MMAVF) which re-ruptured during admission, and the MMAVF was overlooked as a potential contributor to the initial traumatic IPH for which the patient was admitted. A 49-year old man presented with right temporal IPH following an ATV accident and was found to have a right MMAVF on cerebral angiography. The MMAVF appeared on angiography to be unruptured, and therefore was not immediately treated. Later in admission, the patient suffered a new spontaneous IPH ipsilateral to the MMAVF, suggesting a re-rupture. Endovascular transarterial embolization with ethyl vinyl alcohol resulted in complete obliteration of the MMAVF. The patient tolerated treatment well and went on to make a good recovery as of last post-operative imaging at 8 months. Hence, MMAVFs may be present in the setting of IPH following a traumatic brain injury which warrants maintaining a high level of suspicion and low threshold for intervention as they can cause secondary spontaneous intracranial hemorrhage. The absence of notable subdural or extradural hemorrhage on imaging should not exclude rupture. Transarterial embolization with an ethylene vinyl alcohol copolymer is an effective treatment modality.